2017
DOI: 10.1371/journal.pone.0190313
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vegetation phenology on the Mongolian Plateau and their climatic determinants

Abstract: Climate change affects the timing of phenological events, such as the start, end, and length of the growing season of vegetation. A better understanding of how the phenology responded to climatic determinants is important in order to better anticipate future climate-ecosystem interactions. We examined the changes of three phenological events for the Mongolian Plateau and their climatic determinants. To do so, we derived three phenological metrics from remotely sensed vegetation indices and associated these wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…A similar conclusion based on species‐level observations was draw in eastern China (Chen et al , ), the TP (Zhu et al , ), and the western United States (Munson and Long, ). On the landscape scale based on the satellite data, a similar conclusion that the warmer temperature accelerated the green‐up of grassland was also reported (Miao et al , ; Cheng et al , ; Wilsey et al , ). From the perspective of the plant physiology, the phenology could respond to the temperature sensitively because plants can precisely sense the absolute and gradual changes in the diurnal and seasonal temperatures with a wide array of thermosensors (Bahuguna and Jagadish, ).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…A similar conclusion based on species‐level observations was draw in eastern China (Chen et al , ), the TP (Zhu et al , ), and the western United States (Munson and Long, ). On the landscape scale based on the satellite data, a similar conclusion that the warmer temperature accelerated the green‐up of grassland was also reported (Miao et al , ; Cheng et al , ; Wilsey et al , ). From the perspective of the plant physiology, the phenology could respond to the temperature sensitively because plants can precisely sense the absolute and gradual changes in the diurnal and seasonal temperatures with a wide array of thermosensors (Bahuguna and Jagadish, ).…”
Section: Discussionsupporting
confidence: 70%
“…Our results indicated that the light intensity exerted a significant effect on only 9.7% of the time series. This result is consistent with the result from the remote sensing data, which showed that the relationship between light intensity and the SOS was only significant in 19.1% of grassland pixels (Miao et al , ). Thus, the impact of light intensity on the spring phenology might be weak and indirect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear regression analysis on SOS shows similar results that only around 30% of the plants displayed significant trends in SOS over the study period, yet the directions of these trends are divergent ( Figure 2). This can be supported by a recent study using remote sensing approach and reporting the SOS across 70% of the grasslands in the Mongolian Plateau did not significantly change from 1982 to 2011 (Miao et al, 2017). Even so, numerous other studies based on remote sensing data have suggested an overall advanced SOS under warming climates across biomes in the NH (Cong et al, 2013;Piao et al, 2015;Zhao et al, 2015).…”
Section: Changes In Sosmentioning
confidence: 59%